A Review on Smoothing Techniques in Markov Chains Methods - Abdul Rahim, Rahela; Jamaluddin, Fadhilah; Ibrahim, Haslinda; Nadhar Khan, Sahubar Khan (2014)
Markov chains have been suggested since the early sixties for modeling manpower flow, mostly in governmental and public agencies. Numerous books and articles have proclaimed Markov chains as a superior forecasting technique. The flow of data for a consecutive number of years has been the main subject of interest for Markov chains method. Recently, smoothing techniques have been introduced in Markov chain method. This paper aims to review those smoothing technique and analyze their potential in enhancing the conventional Markov chain method